2016
DOI: 10.1371/journal.pone.0159601
|View full text |Cite
|
Sign up to set email alerts
|

miR-9 Acts as an OncomiR in Prostate Cancer through Multiple Pathways That Drive Tumour Progression and Metastasis

Abstract: Identification of dysregulated microRNAs (miRNAs) in prostate cancer is critical not only for diagnosis, but also differentiation between the aggressive and indolent forms of the disease. miR-9 was identified as an oncomiR through both miRNA panel RT-qPCR as well as high-throughput sequencing analysis of the human P69 prostate cell line as compared to its highly tumorigenic and metastatic subline M12, and found to be consistently upregulated in other prostate cell lines including DU-145 and PC3. While miR-9 ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
48
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 54 publications
3
48
1
Order By: Relevance
“…Given the importance of inflammation in the development of HCC, the identification of one of the SOCS family members as a tumor suppressor for liver cancer is particularly relevant. SOCS5 was found to be downregulated in normal endothelial cells showing a miR-9-mediated enhanced endothelial cell migration and was validated as a miR-9 target, 26,39 suggesting its potential role as a tumor suppressor. In addition, the Drosophila orthologue of SOCS5, SOCS36E, behaves as a tumor suppressor in EGFR-driven tumor models.…”
Section: Discussionmentioning
confidence: 97%
“…Given the importance of inflammation in the development of HCC, the identification of one of the SOCS family members as a tumor suppressor for liver cancer is particularly relevant. SOCS5 was found to be downregulated in normal endothelial cells showing a miR-9-mediated enhanced endothelial cell migration and was validated as a miR-9 target, 26,39 suggesting its potential role as a tumor suppressor. In addition, the Drosophila orthologue of SOCS5, SOCS36E, behaves as a tumor suppressor in EGFR-driven tumor models.…”
Section: Discussionmentioning
confidence: 97%
“…MiR‐9 has been demonstrated to be involved in tumorigenesis and development . A recent study has reported that miR‐9 is up‐regulated and acts as a pro‐metastatic miRNA in breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…MiR‐9 has various expression patterns in diverse human cancers, and it plays different roles in different cancer types . Xu et al .…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs regulate gene expression by base-pairing with the 3' untranslated regions (3'UTRs) of their target genes, resulting in translational suppression or mRNA degradation, and ultimately controlling the protein expression of target genes (7). It has previously been demonstrated that miRNAs are important in various biological processes, including cell proliferation, cell cycle, differentiation and metastasis (8)(9)(10). miRNAs have been reported to be downregulated or upregulated in a variety of human malignancies (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%